Association between dependency on community resources and social support among elderly people living in rural areas in China: a cross-sectional study - Ayizuhere Aierken; XiWen Ding; YiYang Pan; Yuan Chen; Ying Li (BMC Geriatrics, 2022)
Abstract Background The prevalence of dependency personality disorder (DPD) is high among elderly people living in rural areas. This study aims to explore the association between dependency on community resources and social support among elderly individuals living in rural areas. Methods A cross-sectional study was conducted in 26 locations in China. A total of 1160 participants aged ≥ 60 years were selected using a complex multistage sampling design. All data were obtained using questionnaires via face-to-face interviews. DPD was measured using the Minnesota Multiphasic Personality Inventory-II in the standardized Chinese version. Self-efficacy was assessed using the Chinese version of the General Self-Efficacy Scale. Social support was measured using the Chinese version of the questionnaires of the Older American Resources and Services scale. Community services and resources comprised 44 items. The association between DPD and levels of social support and self-efficacy was evaluated using a logistic regression model. The association between social support and self-efficacy was assessed using analysis of covariance. Results Univariate analysis results showed that elderly people living in rural areas had higher DPD scores and lower levels of self-efficacy compared with those living in urban areas (P < 0.001). Logistic regression analysis showed that DPD was positively associated with the received frequencies of community health service, contracted family doctor services, and regular lectures on health knowledge among the elderly people with odd ratios of 1.58 (P < 0.001), 2.03 (P = 0.013), and 2.67 (P = 0.005), respectively. Logistic regression analysis showed significant interaction between social support and self-efficacy effect on DPD was found in the additive model (P < 0.001). Conclusion DPD was associated mainly with the community resources among elderly people living in rural areas. Social support and self-efficacy were commonly associated with DPD through a synergistic effect. These results suggest that DPD among elderly people may be reduced through effective social support to directly and indirectly promote the elderly’s use of community resources and improve their self-efficacy.